Answer:
The original equation must have been:
![7x^{2} -5x-2=0](https://tex.z-dn.net/?f=7x%5E%7B2%7D%20-5x-2%3D0)
Step-by-step explanation:
A quadratic equation is in the form of :
![ax^{2} +bx+c=0](https://tex.z-dn.net/?f=ax%5E%7B2%7D%20%2Bbx%2Bc%3D0)
And it is solved in the form of :
and
Now the given equation is :
![x=\frac{-(-5)+-\sqrt{(-5)^{2} -4(7)(-2)} }{2(7)}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-%28-5%29%2B-%5Csqrt%7B%28-5%29%5E%7B2%7D%20-4%287%29%28-2%29%7D%20%7D%7B2%287%29%7D)
We can see that here;
a = 7
b = -5
c = -2
So, the original equation must have been:
![7x^{2} -5x-2=0](https://tex.z-dn.net/?f=7x%5E%7B2%7D%20-5x-2%3D0)
See attached for the solution
I would personally take the number three and trow it out the window but that's not what we are talking about